Composite slurry suitable for sodium-ion battery diaphragm, coating slurry comprising composite slurry and composite diaphragm suitable for sodium-ion battery

By developing composite slurry suitable for sodium ion battery separators, using a variety of sodium salt components to improve the density and stability of the SEI film, the problems of low cycle life and charge and discharge rate of sodium ion battery are solved, and the battery performance is significantly improved.

CN119552547AActive Publication Date: 2025-03-04QINGDAO ZHONGKEHUALIAN ADVANCED MATERIAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411742432.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-04
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The cycle life and charge and discharge rate of sodium ion batteries are low, and the sodium ion battery separator has poor wetting properties on the electrolyte, resulting in poor battery performance.

Method used

A composite slurry suitable for sodium ion battery separators is developed, including sodium salts that are hard to dissolve in water (component A), sodium-containing complexes (component B), sodium-containing organics (component C) and sodium salts that are soluble in water (component D). Through the combination of these components, the density and stability of the SEI membrane are improved, and the heat resistance of the membrane and the wetting properties of the electrolyte are improved.

Benefits of technology

It significantly improves the cycle life and charge and discharge rate of sodium ion batteries, reduces the consumption of electrolyte and electrode materials, and improves the capacity retention rate and low-temperature discharge capacity of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005162855540000111
    Figure BDA0005162855540000111
  • Figure BDA0005162855540000121
    Figure BDA0005162855540000121
  • Figure BDA0005162855540000131
    Figure BDA0005162855540000131
Patent Text Reader

Abstract

The invention provides a composite slurry suitable for a sodium-ion battery diaphragm, a coating slurry comprising the composite slurry and a composite diaphragm suitable for a sodium-ion battery. The composite slurry suitable for the sodium-ion battery diaphragm comprises the following components in percentage by mass: 0-95% of a component A, 0-60% of a component B, 0-10% of a component C, 0-10% of a component D and the balance of water and an auxiliary agent, the component A is a water-insoluble sodium salt; the component B is a sodium-containing complex; the component C is a sodium-containing organic matter; the component D is a water-soluble sodium salt; the component A, the component B, the component C and the component D are not 0 at the same time. The coating slurry suitable for the sodium-ion battery diaphragm comprises the composite slurry. The composite diaphragm comprises a diaphragm base material and the coating slurry coated on the surface of the diaphragm base material. According to the slurry provided by the invention, the SEI film with higher stability is formed, so that the problem of secondary dissolution or decomposition of the SEI film of the sodium-ion battery is avoided, the cycle performance of the current sodium battery is remarkably improved, the first efficiency is improved, the cycle life is prolonged, and the capacity attenuation is greatly reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a composite slurry suitable for a sodium ion battery diaphragm, a coating slurry thereof, and a composite diaphragm suitable for a sodium ion battery. Background Art

[0002] Sodium-ion batteries, a cutting-edge secondary battery technology, have become a major research hotspot in the field of energy storage. Although their working principle is quite similar to that of lithium-ion batteries, sodium-ion batteries have shown unique advantages in material selection and application areas. Their high efficiency, safety, and environmental protection make them have huge development potential in the future energy market. The core advantage of sodium-ion batteries lies in their abundant resources and low cost. These two characteristics make them attract much attention in large-scale application fields such as new energy vehicles, energy storage systems, and smart grids.

[0003] However, sodium-ion batteries themselves also face some shortcomings. The first problem is that the cycle life of sodium-ion batteries needs to be improved. Cycle life refers to the number of times a battery can maintain stable performance during the charge and discharge process. During the charge and discharge process of sodium-ion batteries, the insertion and extraction of sodium ions will cause changes in the structure of the electrode material, thereby affecting the cycle stability of the battery. Although researchers are improving the cycle life of sodium-ion batteries by improving electrode materials and optimizing battery structure, at present, this problem is still one of the important factors restricting its widespread application.

[0004] The charge and discharge rate is another challenge facing sodium-ion batteries. The charge and discharge rate refers to the amount of electricity that can be charged or discharged from the battery per unit time. For application scenarios that require fast charging and discharging, such as grid energy storage, emergency power supply, etc., the charge and discharge rate of the battery is crucial. Due to the relatively slow diffusion rate of sodium ions, the rate of sodium-ion batteries during the charge and discharge process is limited. Although the charge and discharge rate of sodium-ion batteries can be improved to a certain extent by improving the electrolyte and increasing the conductivity of electrode materials, there is still a long way to go to reach the level of lithium-ion batteries.

[0005] In terms of sodium-ion battery separators, sodium-ion batteries in the laboratory development stage generally use glass fiber membranes, while in commercial applications, polyolefin separators used in lithium-ion batteries can be directly replaced and used in sodium-ion batteries. Because the solvents of sodium-ion electrolytes are different, some dry membranes and wet membranes need to be coated with ceramics or other materials to improve the wettability of sodium battery electrolytes to the separators. In addition, the SEI film formed in sodium-based electrolytes is generally unstable due to the high solubility of the SEI film components. Since most inorganic sodium present in the SEI film has a higher solubility than their lithium analogs, NaF has a higher solubility than LiF, and Na2CO3 has a higher solubility than Li2CO3, so the SEI film formed by conventional sodium batteries is not stable.

[0006] In view of this, the present invention is proposed. Summary of the invention

[0007] The purpose of the present invention is to provide a composite slurry suitable for a sodium ion battery diaphragm, including a coating slurry thereof and a composite diaphragm suitable for a sodium ion battery, and to develop a composite diaphragm that is more suitable for the current sodium ion battery electrolyte system by modifying the diaphragm end, thereby improving the above-mentioned problems existing in the current sodium ion battery and improving the cycle life and charge and discharge multiples of the sodium ion battery.

[0008] In order to achieve the above objectives, the present invention particularly adopts the following technical solutions:

[0009] A composite slurry suitable for a sodium ion battery separator, wherein the composite slurry comprises, by mass fraction: 0-95% component A, 0-60% component B, 0-10% component C, 0-10% component D, and the remainder is water and an auxiliary agent;

[0010] The component A is a sodium salt that is poorly soluble in water; preferably, the component A comprises: one or more of sodium bismuthate, sodium trititanate, sodium hexahydroxyantimonate, sodium uranyl zinc acetate, sodium trititanate, sodium hexafluorosilicate, sodium zirconate, sodium borate calcite, sodium metabismuthate, sodium H acid monosodium = 1-amino-6-sulfonic acid-8-naphthol-3-sulfonate, sodium antimonate, sodium uranate, and dipotassium sodium hexanitrite cobalt (III) acid;

[0011] During battery formation, component A can provide initial sites in the SEI film formation process, further inducing the formation of the SEI film. The amount and distribution of component A will affect the density and uniform stability of the final SEI film. Unlike lithium-ion battery systems, the main components of the SEI film formed after formation in conventional sodium-ion battery systems are NaF and Na2CO3. Compared with lithium compounds of the same category, these two have poor stability in the electrolyte and are easily dissolved secondary, causing irreversible losses in the capacity and cycle of sodium-ion batteries. The passivation layer composite compound formed with component A as the initial site has further improved stability, and the SEI film has better density, is continuous and uniform, and prevents other side reactions and self-discharge.

[0012] The component B is a sodium-containing complex; preferably, the component B includes one or more of sodium aluminosilicate, sodium feldspar, and sodium metal organic framework;

[0013] The sodium-containing complex of component B has a certain hardness and chemical inertness, as well as good high temperature resistance. It is not easy to decompose at high temperatures and has significant inorganic metal oxide properties. The slurry coating constructed with this as the main body not only has the function of assisting in the construction of the SEI film, but also the formed coating structure can support the diaphragm and improve the heat shrinkage resistance of the diaphragm material.

[0014] However, such substances have requirements for the molar mass of the sodium element. In component B, the molar mass ratio of non-sodium substances to sodium substances is preferably 1.5-5.0. When the ratio is too low, the proportion of sodium substances is too high, the component material is easily hydrolyzed, the instability is too high, and a heat-resistant support coating cannot be formed; when the ratio is too high, the proportion of non-sodium substances is too high, the SEI film is uneven during the electrochemical process, or the film-forming effect cannot be effectively exerted.

[0015] When component B is used at the same time, its particle size D50 is preferably ≤1 um; because if D50 is too high, the stacking gaps between coating particles will be too large, and the uniformity will be worse, which will cause the SEI film to be uneven.

[0016] The component C is a sodium-containing organic matter; preferably, the component C includes a sodium-containing organic matter having a carbon chain of more than 4C and less than 12C, or containing less than 8 methyl groups;

[0017] Further preferably, the component C includes one or more of sodium ethoxide, sodium propoxide, sodium acetate, sodium propionate, sodium amino acid, sodium valerate, sodium 2,2-dimethylpropoxide, and saturated fatty acid salts;

[0018] The role of component C is first to assist in providing film-forming sites; secondly, compounding with other components can enhance the spatial steric hindrance of the overall material, enhance the suspension ability of particles, and enhance the stability of the system; at the same time, compounding with other slurries can enhance the floating ability of the overall components. After drying, the sodium-rich components are more easily concentrated on the surface of the mixed coating.

[0019] The proportion of component C in the composite slurry is ≤10wt%. Too high a content of component C will also lead to uneven SEI film in the system, and at the same time reduce the density and chemical stability of the SEI film, and there is a risk of secondary decomposition of the SEI film.

[0020] The component D is a sodium salt soluble in water; preferably, the component D comprises: sodium bicarbonate, sodium dihydrogen hypophosphite, methyl orange, sodium fluorosilicate, sodium perborate, lasalocid sodium, monensin sodium, and amaranth;

[0021] First, component D can replenish the sodium content in the system. The sodium material in the soluble sodium salt is more likely to participate in the formation of the SEI membrane, which is more conducive to reducing the consumption of sodium in the electrolyte and has a sodium replenishing effect. Secondly, adding component D can make the sodium-containing components in the system carry a negative charge, thereby improving their dispersion effect in the slurry system.

[0022] Component D accounts for ≤10wt% in the composite slurry, because the sodium element in component D is too active, which can easily lead to an increase in the moisture content of the coating and increase the risk of side reactions; at the same time, component D is suitable as an auxiliary substance for film formation, but not suitable as the main material for film formation, because the stability of the SEI film produced with D as the site is worse than that of the SEI produced with component A as the site, and it is not suitable to be added too much.

[0023] The purity of component A, component B, component C and component D is required to be ≥99.0%, and the particle size is required to be Dv10 ≥0.2um and Dv90 ≤4um;

[0024] The auxiliary agent includes a dispersant and / or an anti-settling agent;

[0025] Wherein, the component A, component B, component C and component D are not 0 at the same time.

[0026] Optionally, the composite slurry comprises, by mass fraction: 3-45% component A, 0-10% component C, 0-10% component D, and the balance is water and additives. Preferably, the composite slurry comprises: 3-45% component A, 0.5-4% component C, 0.1-4% component D, and the balance is water and additives.

[0027] The formulation is preferably suitable for application on existing polyolefin separators or separator coatings.

[0028] Na (a) X (b), wherein Na represents the Na atom in the composite slurry formula, a represents the number of Na atoms; X represents the non-Na atom in the composite slurry formula, and b represents the sum of the number of non-Na atoms. In this formula, a / b is preferably ≥ 0.5 / 10; the further preferred a / b range is between 1 / 10 and 6 / 10. If the a / b value is too small, the coating cannot provide enough initial sites for the formation of the SEI film, which will cause the formed SEI film to be not dense enough, and the stability is insufficient and easy to disintegrate; if the a / b value is too high, Na is a highly active element, which is easy to absorb water and increase side reactions in the battery system.

[0029] Optionally, the composite slurry comprises, by mass fraction: 20-95% component A, 0-10% component C, 0-10% component D, and the balance is water and additives. This formula is suitable as an additive, added to the existing diaphragm coating slurry for doping and then used for coating;

[0030] Na (a) X (b) , where Na represents Na atoms in the composite slurry formula, a represents the number of Na atoms; X represents non-Na atoms in the composite slurry formula, and b represents the sum of the number of non-Na atoms. In this scheme, a / b is preferably ≥ 2.5 / 10; this formula is preferably used as an additive for conventional coating slurry; if the a / b value is too small, the added product cannot play a role in improving the formation of SEI film.

[0031] Optionally, the composite slurry comprises, by mass fraction: 0-50% component A, 5-60% component B, 0-10% component C, 0-10% component D, and the remainder is water and additives. This formula composition can be directly applied to existing conventional diaphragms or coatings, and can also be used as an additive to existing conventional slurries.

[0032] Na (a) X (b) , where Na represents the Na atom in the composite slurry formula, a represents the number of Na atoms; X represents the non-Na atom in the composite slurry formula, and b represents the sum of the number of non-Na atoms. The formula preferably has a / b ≥ 0.25 / 10, and the molar mass ratio of non-sodium substances to sodium substances in the system is between 1.5-5.0. a / b ≥ 0.25 / 10 ensures that the coating can provide sufficient initial sites, and the molar mass ratio of non-sodium substances to sodium substances is between 1.5-5.0, which mainly ensures the chemical stability and thermal stability of the coating material, improves environmental tolerance, and ensures heat resistance.

[0033] The present invention also provides a coating slurry suitable for a sodium ion battery separator, wherein the coating slurry comprises the composite slurry; and the preparation method of the coating slurry comprises method 1 and method 2:

[0034] Wherein, the method 1 comprises:

[0035] S1: mixing the dispersant, anti-settling agent and water, stirring to a clear solution, adding component A, component B, component C and component D to the clear solution in a certain ratio to obtain a dispersion, namely the composite slurry;

[0036] S2: diluting the dispersion obtained in S1 with pure water to a solid content of 3-40wt%, and then adding adhesive 1 and a wetting agent in sequence to obtain the coating slurry;

[0037] Preferably, the composite slurry in the method 1 comprises: 3-45% component A, 0-10% component C, 0-10% component D, and the balance is water and additives;

[0038] Alternatively, the composite slurry in the method 1 comprises: 0-50% component A, 5-60% component B, 0-10% component C, 0-10% component D, and the balance is water and additives;

[0039] The second method comprises:

[0040] S1: mixing the dispersant, anti-settling agent and water, stirring to a clear solution, adding component A, component B, component C and component D to the clear solution in a certain ratio to obtain a dispersion, namely the composite slurry;

[0041] S2: Adding adhesive 2 to the dispersion obtained in S1; preferably, the amount of adhesive 2 is 0-2wt% of the coating slurry;

[0042] S3: adding the mixed system obtained in S2 as a whole as an additive to the precursor coating slurry, wherein the amount of the additive is 2-20wt% of the precursor coating slurry; the precursor coating slurry includes an organic coating slurry and an inorganic coating slurry.

[0043] The organic coating slurry is preferably: an adhesive coating slurry with a polymer including PVDF and PMMA as the main material; the inorganic coating slurry is preferably: a heat-resistant coating slurry with alumina or boehmite as the main material;

[0044] The composite slurry prepared by the second method of the present invention is equivalent to an additional additive of a slurry and can be used in any known or unknown coating slurry.

[0045] Preferably, the amount of component B in the method 2 is 0;

[0046] Further preferably, the composite slurry in the second method comprises: 20-95% component A, 0-10% component C, 0-10% component D, and the remainder is water and additives.

[0047] The dispersant is selected from one or more of polycarboxylic acid ammonium salt, polycarboxylic acid sodium salt, polyacrylate, and phosphate ester; the amount of the dispersant added is 0.5-5wt% of the dispersion;

[0048] The anti-settling agent is selected from one or more of sodium carboxymethyl cellulose, cellulose, PVP, polyurethane block copolymers, polyacrylate copolymers, and polyvinyl pyrrolidone; the amount of the anti-settling agent added is 0.5-5wt% of the dispersion;

[0049] The adhesive 1 comprises: one or more of an emulsion-type acrylate-based polymer, a solution-type acrylate-based polymer, a polyurethane-based polymer, a polyacrylamide-based polymer, a polyimide-based polymer, and a polyamide-based polymer; the amount of the adhesive 1 added accounts for 1-20wt% of the obtained coating slurry;

[0050] The wetting agent includes one or more of an organosilicon-modified wetting agent, a polyether wetting agent, an acetylene alcohol wetting agent, and an alcohol wetting agent; the amount of the wetting agent added accounts for 0.01-2.5% of the obtained coating slurry;

[0051] The second adhesive may be the adhesive in the precursor coating slurry, or one or more of an emulsion-type acrylate-based polymer, a solution-type acrylate-based polymer, a polyurethane polymer, a polyacrylamide polymer, a polyimide polymer, and a polyamide polymer.

[0052] Preferably, after step S1 and before step S2, the method further comprises: adding a hydrophobic additive to the dispersion to modify it and / or grinding the dispersion with a sand mill;

[0053] The hydrophobic auxiliary agent includes a coupling agent and a hydrophobic polymer, and the modification includes: adding the coupling agent and the hydrophobic polymer to the obtained dispersion, dispersing them uniformly, and then keeping them at 30-70° C. for 2-4 hours to perform hydrophobic modification;

[0054] The coupling agent is selected from: one or more of organic chromium complexes, silanes, titanates, and aluminate compounds;

[0055] The hydrophobic polymer is selected from one or more of: olefin-modified polymers containing hydrophobic groups, acrylonitrile polymers, acrylate polymers, and methacrylate polymers;

[0056] The amount of the hydrophobic additive added is 0.5-5wt% of the dispersion;

[0057] Preferably, the coupling agent is added in an amount of 0-2 wt % of the dispersion;

[0058] By performing hydrophobic modification, grafting modification is performed on the surface, and at the same time, the hydrophilic groups on the original surface of the component are consumed, so that the whole component is finally hydrophobic;

[0059] The diameter of the zirconium ball of the sand mill is 500-1000 times the particle size of the component A, component B, component C, and component D. Sand milling can make the components in the system disperse and modify more evenly, improve the overall consistency of the system, and prevent large particles from agglomerating, resulting in sodium precipitation in the product.

[0060] The present invention also provides a composite diaphragm suitable for a sodium ion battery, wherein the composite diaphragm comprises a diaphragm substrate and the coating slurry provided by the present invention coated on the surface of the diaphragm substrate.

[0061] The preparation method of the composite diaphragm comprises: coating the diaphragm substrate with the coating slurry prepared by the composite slurry provided by the present invention to form a composite diaphragm, the coating surface can be coated on the positive electrode side, the negative electrode side or both sides of the positive and negative electrodes, any coating of the composite diaphragm contains the slurry provided by the present invention, and then drying and rolling to obtain the composite diaphragm suitable for sodium ion batteries. The diaphragm substrate comprises any one of a wet-process polyolefin porous membrane, a dry-process polyolefin porous membrane, a spinning composite porous membrane, and a non-woven porous membrane.

[0062] Optionally, the coating method can be any one of micro-concave roller coating, anilox roller coating, spray coating, spot coating, dip coating, slit coating, and screw extrusion coating.

[0063] During the drying process, the oven temperature ranges from 40 to 90°C.

[0064] The present application also provides a sodium ion secondary battery prepared using the composite diaphragm suitable for sodium ion batteries provided in the present application, which also includes a positive electrode, a negative electrode and an electrolyte.

[0065] The present application also provides a battery module, which includes the sodium ion secondary battery provided in the present application.

[0066] The present application also provides a battery pack, which includes the battery module provided in the present application.

[0067] The present application also provides an electrical device, which includes a combination of one or more of the sodium ion secondary battery, the battery module, and the battery pack provided in the present application.

[0068] By applying the composite slurry of the present application to the battery separator end, the cycle life and charge and discharge rate of the sodium ion secondary battery are significantly improved.

[0069] The composite slurry and coating slurry provided in this application are coated on the current commercial diaphragm to prepare the composite diaphragm, or the composite diaphragm obtained by coating on other main bodies can improve the wettability of the electrolyte, and can prevent the electrolyte and electrode materials from further reacting, thereby reducing the consumption of electrolyte and electrode materials by more than 90%. The interfacial compatibility between the diaphragm-electrolyte-electrode material is improved, making the sodium ion transmission more uniform and lower in impedance throughout the interface, increasing the diffusion rate of sodium ions, and significantly improving the charge and discharge rate, thereby improving the rate performance and cycle life of the secondary sodium battery.

[0070] The SEI film formed in the present application is denser and more stable in the electrolyte. The components therein will not dissolve secondary in the electrolyte, and will not cause capacity attenuation and cycle performance loss to the battery at the product design level.

[0071] Compared with the prior art, the present invention has the following beneficial effects:

[0072] The composite slurry provided in the present application, whose main components can provide initial sites for the growth of SEI film, and induce SEI to form a denser layer structure, preventing further reaction of electrolyte and electrode materials, thereby reducing the consumption of electrolyte and electrode materials by more than 90%, reducing the loss of energy density of sodium ion batteries, and improving battery capacity and cycle performance.

[0073] The coating slurry prepared using the composite slurry provided in the present application has higher stability in the electrolyte, and the components therein will not dissolve secondary in the electrolyte, and will not cause capacity decay and cycle performance loss at the product design level of the battery, thereby making the capacity retention rate of the sodium battery after a long cycle higher.

[0074] The composite diaphragm provided in the present application has a better compatibility between the diaphragm coating and the electrolyte, which can guide the sodium ions to deposit evenly on the negative electrode interface, make the sodium ions more evenly distributed on the interface, make the sodium ions more evenly transmitted throughout the interface and have lower impedance, thereby increasing the diffusion rate of sodium ions and significantly increasing the charge and discharge rate; at the same time, the wettability of the electrolyte is improved, the contact angle between the sodium ion battery electrolyte and the diaphragm is ≤30°, and the wettability is improved by more than 200% compared with conventional polyolefin dry-process membrane substrates, more than 100% compared with conventional polyolefin wet-process membrane substrates, and more than 50% compared with conventional ceramic-coated composite membranes. DETAILED DESCRIPTION

[0075] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0076] Example 1

[0077] This embodiment provides a composite slurry suitable for sodium ion battery separator, which is composed of: by mass fraction, the composite slurry includes: 5% sodium borate calcite, 4% sodium uranyl zinc acetate, 1% sodium valerate, 0.5% sodium bicarbonate, appropriate amounts of polycarboxylate ammonium salt, sodium carboxymethyl cellulose and water. (a) X (b) The a / b value range is 3-4 / 10. Among them, the final overall Dv50 particle size range of sodium borate calcite, sodium uranyl zinc acetate, sodium valerate, and sodium bicarbonate is 0.2-0.4um

[0078] This embodiment also provides a coating slurry including the composite slurry and the prepared composite diaphragm, and the preparation steps are as follows:

[0079] S1: The polycarboxylate ammonium salt (0.5% by mass), sodium carboxymethyl cellulose (0.5% by mass) and water (balance by mass) are mixed and stirred to a clear solution, and 5% sodium borate calcite, 4% sodium uranyl zinc acetate, 1% sodium valerate and 0.5% sodium bicarbonate are added to the clear solution to obtain a dispersion, which is the composite slurry;

[0080] S2: diluting the dispersion obtained in S1 with pure water to a solid content of 6 wt %, and then sequentially adding 1 wt % of an emulsion-type acrylate-based polymer and 0.04 wt % of an organosilicon-modified wetting agent to obtain the coating slurry;

[0081] S3: The coating slurry prepared in S2 is coated on one side of a polyolefin separator substrate with a thickness of 9 μm, and the coating thickness is 1.0 μm. After drying at 60° C., the composite separator suitable for sodium ion batteries is obtained by rolling up.

[0082] Example 2

[0083] This embodiment provides a composite slurry suitable for sodium ion battery separator, which is composed of: in terms of mass fraction, the composite slurry includes: 4% sodium bismuthate, 3% sodium trititanate, 1% sodium valerate, 0.5% sodium bicarbonate, polycarboxylic acid ammonium salt (0.5% by mass), sodium carboxymethyl cellulose (0.2% by mass) and water (balance by mass). (a) X (b) The a / b value range is 5-6 / 10. Among them, the particle size of sodium bismuthate, sodium trititanate, sodium valerate, and sodium bicarbonate is 0.2-0.5um;

[0084] This embodiment also provides a coating slurry including the composite slurry and the prepared composite diaphragm, and the preparation steps are as follows:

[0085] S1: Mixing polycarboxylic acid ammonium salt (0.5% by mass), sodium carboxymethyl cellulose (0.2% by mass) and water (balance by mass), stirring to a clear solution, adding 5% sodium borate calcite, 4% sodium uranyl zinc acetate, 1% sodium valerate, and 0.5% sodium bicarbonate to the clear solution to obtain a dispersion, namely the composite slurry;

[0086] S2: diluting the dispersion obtained in S1 with pure water to a solid content of 10 wt %, and then sequentially adding 2 wt % of an emulsion-type acrylate-based polymer and 0.06 wt % of an organosilicon-modified wetting agent to obtain the coating slurry;

[0087] S3: Coat the coating slurry prepared in S2 on one side of the diaphragm substrate, wherein the diaphragm substrate is a polyolefin diaphragm coated with a ceramic coating on the surface, wherein the ceramic coating has a thickness of 2 μm, and the thickness of the polyolefin diaphragm itself is 9 μm. The coating thickness of the coating slurry provided in the present application is 1.0 um, and then dry it at 60°C and roll it up to obtain a composite diaphragm suitable for sodium ion batteries.

[0088] Example 3

[0089] According to the same or similar method as in Example 1 or 2, several composite slurries, coating slurries and composite diaphragms are provided, and the specific formulas and parameters are shown in Table 1 below:

[0090] Table 1 Composite slurry formula and composite diaphragm parameter table of Examples 3-8

[0091]

[0092]

[0093] Comparative Example 1

[0094] The comparative example is a PE-based film with a thickness of 9 μm.

[0095] Comparative Example 2

[0096] This comparative example is a diaphragm formed by coating a 3 μm ceramic coating on one side of a 9 μm thick PE base film.

[0097] The membranes provided in the examples and comparative examples were used in sodium ion batteries for performance testing:

[0098] 1. Cycle performance test conditions: 2.0-3.8V cycle 1500 times capacity retention rate; Test method: Under normal temperature environment, use a charge and discharge cycle tester to cycle the battery for 1500 cycles at 2.0-3.8V voltage conditions, and record its capacity retention rate;

[0099] 2. Low temperature discharge performance evaluation parameters: -10℃ 1C capacity retention rate; Test method: Place the battery in a specific low temperature environment to cool it to -20℃. Then use a charge and discharge cycle tester to discharge the battery under 1C constant current conditions and record its capacity retention rate;

[0100] 3. Rate discharge evaluation standard: 3C capacity retention rate at room temperature; Test method: At room temperature, use a charge and discharge cycle tester to discharge the battery at a constant current of 3C and record its capacity retention rate.

[0101] The specific test results are shown in Table 2 below:

[0102] Table 2 contains the sodium ion battery performance test table of the membranes provided in the embodiments and comparative examples

[0103]

[0104]

[0105]

[0106] As shown in Table 2, by comparing Examples 1-8 with Comparative Examples 1 and 2, the diaphragms prepared from the slurries of Examples 1-8 have a significant effect on improving the first coulombic efficiency, cycle performance, low-temperature discharge, and rate discharge performance of sodium-ion batteries. The contact angle between the coating and the electrolyte is significantly reduced when a sodium-rich coating or a product containing sodium-rich materials in the coating is added, indicating that the lyophilicity of the coating is improved. The application of sodium-rich materials in diaphragms significantly improves the problem of poor electrical performance faced by current sodium battery systems.

[0107] Among them, Examples 1-4 are sodium-rich material coatings with component A as the main material and the other components as auxiliary materials. This coating is thin in thickness, but can provide more and more stable initial sites. The SEI film finally formed is more compact and uniform, with higher stability, so the electrochemical performance of the product is optimal. However, this coating does not provide improved heat resistance. Examples 5-6 are sodium-rich material dispersions with component A as the main material added to mature ceramic coating slurry. The sodium-rich material is distributed in the original coating. The SEI film finally assisted in forming is not as compact as Examples 1-4, and the electrochemical performance is also poor. However, the mixed coating is formed in one step, which has an advantage in coating cost. Embodiment 7-8 is a sodium-rich material coating with B component material as the main material and other components as auxiliary materials. The density of the SEI film formed by it is lower than that of Embodiment 1-4 due to Embodiment 5-6, and the stability of the SEI film is lower than that of Embodiment 1-4, but the complex material of the B component has a certain hardness and chemical inertness, and at the same time, it has good high temperature resistance, is not easy to decompose at high temperature, and has significant inorganic metal oxide characteristics. The coating material constructed with this as the main body has the function of assisting the construction of the SEI film, and the coating structure formed can support the diaphragm and improve the heat shrinkage resistance of the diaphragm material. All three schemes have a significant improvement on the electrochemical performance of sodium ion batteries, but they have different focuses in terms of function, cost, and heat resistance.

[0108] The slurry component provided by the present application provides an initial site for the growth of the SEI film, and induces the SEI to form a denser layer structure, preventing the electrolyte and the electrode material from further reacting, thereby reducing the consumption of the electrolyte and the electrode material, and making the sodium battery have a more stable coulombic efficiency in a long cycle. At the same time, because the SEI film formed by the present application has a dense structure, a stable chemical structure, and a stronger electrochemical resistance, it solves the problems of low stability, easy secondary dissolution, and discontinuity of the SEI film formed by traditional sodium ion batteries. Significantly improve the cycle life, low temperature discharge capability, and high rate discharge capability of sodium ion batteries.

[0109] Please note that the technical features of the above embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. The above embodiments only express several implementation methods of the present application, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several variations and improvements can be made, which all belong to the scope of protection of the present application. Therefore, the scope of protection of the patent in this application shall be based on the attached claims.

Claims

1. A composite slurry suitable for sodium ion battery separator, characterized in that: The composite slurry comprises, by mass fraction, 0-95% component A, 0-60% component B, 0-10% component C, 0-10% component D, and the remainder is water and additives; The component A is a sodium salt that is poorly soluble in water; the component B is a sodium-containing complex; the component C is a sodium-containing organic matter; the component D is a sodium salt that is soluble in water; the auxiliary agent includes a dispersant and / or an anti-settling agent; Wherein, the component A, component B, component C and component D are not 0 at the same time.

2. The composite slurry according to claim 1, characterized in that: The component A comprises: one or more of sodium bismuthate, sodium trititanate, sodium hexahydroxyantimonate, sodium uranyl zinc acetate, sodium trititanate, sodium hexafluorosilicate, sodium zirconate, sodium borate calcite, sodium metabismuthate, sodium H acid monosodium = 1-amino-6-sulfonic acid-8-naphthol-3-sulfonate, sodium antimonate, sodium uranate, and dipotassium sodium hexanitrite cobalt (III) acid; The component B includes one or more of sodium aluminosilicate, albite, and sodium metal organic framework; The component C includes a sodium-containing organic matter having a carbon chain of more than 4C and less than 12C, or containing less than 8 methyl groups; Preferably, the component C comprises one or more of sodium ethoxide, sodium propoxide, sodium acetate, sodium propionate, sodium amino acid, sodium valerate, sodium 2,2-dimethylpropoxide, and saturated fatty acid salts; The component D comprises: sodium bicarbonate, sodium dihydrogen hypophosphite, methyl orange, sodium fluorosilicate, sodium perborate, lasalocid sodium, monensin sodium and amaranth.

3. The composite slurry according to claim 1, characterized in that: Calculated by mass fraction, the composite slurry comprises: 3-45% component A, 0-10% component C, 0-10% component D, and the remainder is water and additives.

4. The composite slurry according to claim 1, characterized in that: Calculated by mass fraction, the composite slurry comprises: 20-95% component A, 0-10% component C, 0-10% component D, and the remainder is water and additives.

5. The composite slurry according to claim 1, characterized in that: Calculated by mass fraction, the composite slurry comprises: 0-50% component A, 5-60% component B, 0-10% component C, 0-10% component D, and the remainder is water and additives.

6. A coating slurry suitable for sodium ion battery separator, characterized in that: The coating slurry comprises the composite slurry according to any one of claims 1-5.

7. The coating slurry according to claim 6, characterized in that: The preparation method of the coating slurry includes method 1 and method 2: The method 1 comprises: S1: mixing the dispersant, anti-settling agent and water, stirring to a clear solution, adding component A, component B, component C and component D to the clear solution in a certain ratio to obtain a dispersion, namely the composite slurry; S2: diluting the dispersion obtained in S1 with pure water to a solid content of 3-40wt%, and then adding adhesive 1 and a wetting agent in sequence to obtain the coating slurry; The second method comprises: S1: mixing the dispersant, anti-settling agent and water, stirring to a clear solution, adding component A, component B, component C and component D to the clear solution in a certain ratio to obtain a dispersion, namely the composite slurry; S2: adding adhesive 2 to the dispersion obtained in S1; S3: adding the mixed system obtained in S2 as a whole to the precursor coating slurry as an additive, wherein the amount of the additive is 2-20wt% of the precursor coating slurry; the precursor coating slurry includes an organic coating slurry and an inorganic coating slurry.

8. The coating slurry according to claim 7, characterized in that: The dispersant is selected from one or more of polycarboxylic acid ammonium salt, polycarboxylic acid sodium salt, polyacrylate, and phosphate ester; the amount of the dispersant added is 0.5-5wt% of the dispersion; The anti-settling agent is selected from one or more of sodium carboxymethyl cellulose, cellulose, PVP, polyurethane block copolymers, polyacrylate copolymers, and polyvinyl pyrrolidone; the amount of the anti-settling agent added is 0.5-5wt% of the dispersion; The adhesive 1 comprises: one or more of an emulsion-type acrylate-based polymer, a solution-type acrylate-based polymer, a polyurethane-based polymer, a polyacrylamide-based polymer, a polyimide-based polymer, and a polyamide-based polymer; the amount of the adhesive 1 added accounts for 1-20wt% of the obtained coating slurry; The wetting agent includes one or more of an organosilicon-modified wetting agent, a polyether wetting agent, an acetylene alcohol wetting agent, and an alcohol wetting agent; the amount of the wetting agent added accounts for 0.01-2.5% of the obtained coating slurry; The second adhesive includes an adhesive of the original formula component, or one or more of an emulsion-type acrylate-based polymer, a solution-type acrylate-based polymer, a polyurethane polymer, a polyacrylamide polymer, a polyimide polymer, and a polyamide polymer.

9. The coating slurry according to claim 7, characterized in that: After step S1 and before step S2, the method further includes: adding a hydrophobic additive to the dispersion to modify it and / or grinding the dispersion with a sand mill; The hydrophobic auxiliary agent includes a coupling agent and a hydrophobic polymer, and the modification includes: adding the coupling agent and the hydrophobic polymer to the obtained dispersion, dispersing them uniformly, and then keeping them at 30-70° C. for 2-4 hours to perform hydrophobic modification; The coupling agent is selected from: one or more of organic chromium complexes, silanes, titanates, and aluminate compounds; The hydrophobic polymer is selected from one or more of: olefin-modified polymers containing hydrophobic groups, acrylonitrile polymers, acrylate polymers, and methacrylate polymers; The amount of the hydrophobic additive added is 0.5-5wt% of the dispersion; Preferably, the coupling agent is added in an amount of 0-2 wt % of the dispersion; The diameter of the zirconium ball of the sand mill is 500-1000 times the particle size of the component A, component B, component C and component D.

10. A composite diaphragm suitable for sodium ion batteries, characterized in that: The composite diaphragm comprises a diaphragm substrate and the coating slurry according to any one of claims 6 to 9 coated on the surface of the diaphragm substrate.

Citation Information

Patent Citations

  • Novel lithium ion battery diaphragm with inorganic coating and preparation method thereof

    CN103107301A

  • NaF / metal composite sodium-supplementing positive electrode active material, positive electrode material, positive electrode, preparation of positive electrode and application of positive electrode in sodium-ion battery

    CN111293288A

  • Composite coating sodium-ion battery diaphragm and preparation method thereof

    CN113675533A

  • Preparation method of Na3Ti2 (PO4) 3 positive electrode and application of Na3Ti2 (PO4) 3 positive electrode in sodium ion battery

    CN115472784A